Ushul Fiqh I - H. Nasrun Harun (Logos, 1996)
ir,Jil.I=c.1/oen, Jil.I=C.2-6/oen, jil.I=C.7/oen, Jil.I=c.8/oen, Jil.I=c.9/oen, Jil. I=c.10-12/ir,jil.1,c.13/Jil.1=c.14/ir,ji.1,c.15/tr, jil.1,c.16/en, c.17-18/en, jil.1=c.17